ENGLISH PHRASES USED IN ACADEMIC WRITING - Feruza Kucharova Alisher kizi; Usmonova Sabrina Siroj kizi (TADQIQOTLAR, 2025)
Abstract:    English phrases play a vital role in academic writing, serving as essential tools to structure arguments, present evidence, and articulate ideas clearly and persuasively.  These  phrases  often  include  connectors,  transitions,  and  signposting language that guide readers through the text. Academic writers use them to express cause  and  effect,  compare  and  contrast,  and  highlight  significance,  among  other functions. Examples include "it is widely acknowledged that," "in contrast to," "the findings suggest that," and "a possible explanation for this is." Mastery of these phrases enhances  the  coherence  and  professionalism  of  academic  work,  making  arguments more accessible to a global audience. Additionally, they allow for nuanced expression and adherence to academic conventions, which are critical for effective communication in scholarly contexts.